Plasma optical modulators for intense lasers - Lu-Le Yu (Nature Portfolio, 2016)
Optical modulators are easily damaged by high-intensity pulses. Here, the authors propose a method for directly modulating high-power laser light across a broad spectral range using a wave generated in a sub-millimetre-scale underdense plasma by a second laser.